Unveiling the Hydrogen Diffusion During Degradation of Silicon Solar Cells - MyeongSeob Sim; Yejin Gu; Donghwan Kim; Yoonmook Kang (Energies, 2025)
We investigated monocrystalline passivated emitter rear contact cells for light- and elevated-temperature-induced degradation. Among the cell performance factors, a short current density results in a significant decrease in the short term. The quantum efficiency is also affected by carrier recombination-active defects, especially in the case of the reference cell, which has a decreased quantum efficiency across the wavelength, unlike the commercial cell. The front side of the cell has a diffuse hydrogen distribution, and it is related to LeTID. We observe how the hydrogen changes during each process and the changes in the profile during the degradation. The hydrogen appears to redistribute within the silicon wafer and saturate at a certain equilibrium state. The hydrogen distribution is correlated with the changes in the lifetime and, finally, short current density. Regeneration occurs depending on the hydrogen concentration within the emitter, and the closer the concentration is to saturation, the less degradation occurs.